Characterizing aviation maintenance manuals written in the controlled language ASD-STE100 as a genre: a corpus analysis - Díaz-Galán, Ana (Complutense Journal of English Studies, 2022)
The texts associated with aircraft maintenance are fundamental in the maintenance process and in aircraft security. Aviation maintenance manuals ‒the core of this documentation‒ have to comply with regulations concerning content, format and expression. To ensure uniformity, manuals abide by a specification which regulates writing practices accommodating them to the controlled natural language ASD-STE100, a simplified version of English used as a standard in the industry. Through the qualitative analysis of a corpus of maintenance texts, this paper characterizes aviation instructions manuals as a genre by (i) illustrating the most relevant restrictions imposed by the specification and their implementation at the surface levels glossed in the specification and (ii) providing a description of the rhetorical macrostructure of instructional texts. The analysis reveals discrepancies between actual use and the rules which concern lexical, phrasal or sentential units; compliance with the rhetorical macrostructure seems to be the norm, however. As an explanation, it is hypothesized that deviations occur in areas where the specification clashes with standard technical writing practice, supporting thus the view that genres are mediated by social practices. Although further quantitative analysis is pending, this description of the use of ASD-STE100 might prove of interest both to scholars and practitioners.